SAT0532 Updated Eular Evidence-Based Recommendations for the Diagnosis of Gout. (10th June 2014) - Richette, P.; Pascual, E.; Doherty, M.; Barskova, V.; Becce, F.; Coyfish, M.; Janssens, H.; Jansen, T.; Lioté, F.; Mallen, C.; Nuki, G.; Perez-Ruiz, F.; et al.
Abstract : Background: Gout has become the most common inflammatory arthritis but is still frequently misdiagnosed. New data on imaging and clinical diagnosis have become available since publication of the first EULAR recommendations for the diagnosis of gout in 2006. This has prompted a systematic review and update of the 2006 recommendations. Objectives: To develop updated evidence-based recommendations for the diagnosis of gout Methods: The 2014 EULAR task force comprised 15 rheumatologists, 1 radiologist, 2 GPs, 2 patients and 2 experts in methodology from 12 European countries. The expert group first voted to determine whether each of the 2006 recommendations for diagnosis should be retained, modified or deleted. MEDLINE, EMBASE and Cochrane Library reports were searched systematically to obtain research evidence from 2005 to 2013 on all aspects of the diagnosis of gout. Internal and external validity of the articles was assessed. The quality of evidence was categorised according to GRADE. The task force was presented with a synopsis of this literature review and generated a first draft of key recommendations after a two-day meeting. Final recommendations were agreed using a Delphi consensus approach. The level of agreement to each recommendation was assessed using EULAR numeral rating scales. Results: A search for crystals in synovial fluid (SF) or tophus aspirates was recommended in every person with suspected gout, because demonstration of monosodium urate (MSU) crystals allows a definitive diagnosis of gout. SF should also be examined for crystals in any arthritis of unknown aetiology. There was consensus that a number of suggestive clinical features supported a clinical diagnosis of gout. These are: mono articular involvement of a foot or ankle joint (especially the first MTP); previous episodes of similar acute arthritis; rapid onset of severe pain and swelling (at its worst in <24 h); erythema; male gender; and associated cardiovascular diseases and hyperuricaemia. When crystal identification is not possible, it was recommended that any atypical presentation should be investigated by imaging, in particular with ultrasound to seek features suggestive of urate deposits (double contour sign and tophi). There was consensus a that a diagnosis of gout should not be based on the presence of hyperuricaemia alone. There was also a strong recommendation that all persons with gout should be systematically assessed for the presence of associated co-morbidities and risk factors for cardiovascular disease, as well as for risk factors for chronic hyperuricaemia. Conclusions: Eight updated, evidence-based, expert consensus recommendations for the diagnosis of gout are proposed. Disclosure of Interest: P. Richette Speakers bureau: Ménarini, Ipsen, Savient, Novartis, Astra-ZenecaM, E. Pascual Speakers bureau: Menarini, Savient, Novartis, Astra Zaneca, M. Doherty Speakers bureau: Menarini, Ardea and Novartis, V. Barskova: None declared, F. Becce: None declared, M. Coyfish: None declared, H. Janssens: None declared, T. Jansen Speakers bureau: Ménarini, F. Lioté Speakers bureau: Novartis, Ipsen, Menarini, SOBI, Mayolly-Spindler, Astra-Zeneca, Ardea, Savient, C. Mallen: None declared, G. Nuki Speakers bureau: Ipsen, Menarini, Novartis and Savient., F. Perez-Ruiz Speakers bureau: Astra-Zeneca, Menarini, Metabolex, Novartis, Pfizer, SOBI, J. Pimentão Speakers bureau: Ménarini, T. Piwell: None declared, L. Punzi Speakers bureau: Ménarini, A. So Speakers bureau: Novartis, SOBI, Astra-Zeneca and Menarini, A.-K. Tausche Speakers bureau: Menarini, Savient, Novartis, Sobi, Ardea Bioscience, T. Uhlig: None declared, J. Zavada Speakers bureau: Ménarini, Novartis, W. Zhang Speakers bureau: Savient, F. Tubach: None declared, T. Bardin Speakers bureau: Ménarini, Ipsen, Savient, Novartis, Astra-Zeneca, SOBI DOI: 10.1136/annrheumdis-2014-eular.5546